Intrapelvic Intestinal Leiomyoma in a Dog - Diagnostic and Therapeutic Challenges - dos Santos, Endreo Alan Pail; Mestieri, Maria Lígia de Arruda; Emanuelli, Mauren Picada; Wojahn, Laís Fernanda; Strey, Fabiana Wurster; dos Anjos, Bruno Leite (Acta Scientiae Veterinariae, 2021)
Background: Rectal tumors are uncommon in dogs and cats. The clinical signs result from intra- and extraluminal compression. Diagnosis and treatment of rectal tumors are challenging due to their intraplevic location. Owing to considerable bone superposition, computed tomography is the best exam to evaluate the tumor and plan surgery; however, poor availability and high costs may hinder its use. The objective of this case report is to describe the successful use of a combination of diagnostic techniques, namely transrectal ultrasound, transrectal fine-needle aspiration, and colonoscopy, for diagnosis and surgery planning in a case of intrapelvic intestinal leiomyoma in a dog. Case: A 13-year-old female mongrel dog with tenesmus, low stool production, and hematochezia for two months was presented for examination. During this two-month period, a symptomatic treatment was administered, but there was no clinical improvement. In the clinical evaluation revealed a painless mass on the left dorsolateral region, at a depth of around 4 cm, with considerable luminal reduction. Abdominal ultrasound revealed a mass close to the descending colon; however, bone superposition precluded identification of its origin or delimitation of its boundaries. The patient was subjected to transrectal ultrasound imaging, colonoscopy, and cytological examination of fine-needle aspiration biopsy material collected under general anesthesia. The mass was located at the final portion of the descending colon; it was extraluminal, and measured around 7 x 7 cm. The integrity of the intestinal wall was preserved. Next, radiographic examination of the thorax using three projections (ventrodorsal, left lateral, and right lateral) was performed to check for metastases, and no alteration was detected. Cytology suggested presence of leiomyoma. The patient underwent exploratory laparotomy with pubic osteotomy for intrapelvic access. The extraluminal mass was found adhered to the dorsal colorectal surface, whose serosa was compromised. The mass, which occupied around 80 to 90% of the pelvic canal, was completely removed and submitted to histopathological examination, which confirmed presence of proliferative neoplastic mesenchymal cells (intestinal leiomyoma). The patient’s clinical picture evolved without intercurrences, and the patient was discharged 40 days after the pubic bone consolidation procedure. Discussion: The occurrence of leiomyomas in the colorectal segment of the intestine is rare in dogs. Neoplasms that develop in such a region of the intestine are usually more frequently found in elderly animals, such as the patient of this report. Leiomyomas are benign (non-invasive) neoplasms with slow growth. Consequently, clinical signs emerge when the mass exhibits a large size, which causes intra- or extraluminal compression, tenesmus, diminished production or absence of defecation, and hematochezia, as observed in the present case. Even though the clinical signs are similar in these cases, they are unspecific; consequently, for reaching a diagnosis, biopsy and histological investigation are required. In spite of the usefulness of these procedures for diagnosis, computed tomography is the exam of choice to investigate neoplasms in intrapelvic intestinal segments because it allows three-dimensional reconstruction of the affected structures and facilitates surgical planning. Unfortunately, computed tomography was not available for this case. Consequently, colonoscopy, transrectal ultrasound, and transrectal fine-needle aspiration biopsy were performed. When combined, these procedures allowed determination of the location, size and type of neoplasm, which were crucial pieces of information for the correct diagnosis and surgical planning, thus contributing for the successful management of the patient.